Perspectives of Non-Moeslim Students On Islamic Education In Postgraduate Program University Muhammadiyah Tangerang - Asrori Mukhtarom (Universitas Muhammadiyah Tangerang, 2023)
Muhammadiyah College is a private university committed to providing modern and inclusive Islamic education. Islamic education is carried out in the form of Al-Islam and Kemuhammadiyahan learning in class and Islamic seminar activities outside the classroom. This research was conducted at the Muhammadiyah University of Tangerang Postgraduate Program. Active students consist of Muslim and non-Muslim students. This study aims to determine the perceptions of non-Muslim students towards Islamic education held by the Postgraduate Program at the University of Muhammadiyah Tangerang. This type of research is descriptive qualitative with observation, interviews and documentation scientifically and naturally. The results of this study indicate that the perceptions of non-Muslim students towards Islamic education are positive perceptions. Non-Muslim students received well the Islamic teaching material presented by the lecturers in the first semester. The perception of non-Muslim students towards Islamic education is a process of building character in accordance with Islamic teachings which are full of peace and uphold human values. In the learning process in the classroom, there are three learning models that are used, namely learning centered on prepared material, teacher-centered and student-centered. Non-Muslim students feel enthusiastic and comfortable while participating in the Islamic education process because they are treated on the same level as other Muslim students. Non-Muslim students received well the Islamic teaching material presented by the lecturers in the first semester. The perception of non-Muslim students towards Islamic education is a process of building character in accordance with Islamic teachings which are full of peace and uphold human values. In the learning process in the classroom, there are three learning models that are used, namely learning centered on prepared material, teacher-centered and student-centered. Non-Muslim students feel enthusiastic and comfortable while participating in the Islamic education process because they are treated on the same level as other Muslim students.